Metabolic Alterations in Adipose Tissue During the Early Phase of Experimental Endotoxemia in Humans - Wellhoener, P.; Vietheer, A.; Sayk, F.; Schaaf, B.; Lehnert, H.; Dodt, C. (Hormone and Metabolic Research, 2011)
Adipose tissue plays an important role in energy homeostasis; however, there is only little knowledge about its metabolic activity during critical illness or sepsis. We assessed adipose tissue metabolic activity and local blood flow during experimental endotoxemia in otherwise healthy humans. In a prospective, placebo controlled and randomized experiment we measured changes in lactate, glycerol, and pyruvate concentrations in microdialysate samples of femoral adipose tissue after an intravenous bolus of lipopolysaccharide (LPS, 4 ng/kg). Intravenous endotoxin caused an early and constant increase in interstitial pyruvate, while formation of lactate in adipose tissue was not affected. In contrast, lactate levels in serum were elevated significantly after 90 min (p<0.05) and likewise, serum glycerol concentrations rose 90 min after LPS treatment (p<0.05) and 60 min earlier than in adipose tissue. Subcutaneous adipose tissue blood perfusion increased 2-fold while there was a strong decline in skin blood flow. Pyruvate accumulation in subcutaneous adipose tissue is an early marker of endotoxemia. While adipose tissue is a major source of serum glycerol and lactate in humans during physiological conditions, it contributes only little to increased serum lactate and glycerol levels during endotoxemia.
Keywords: adipose tissue; metabolism; endotoxemia; sepsis; microdialysis